1984
DOI: 10.1084/jem.160.1.310
|View full text |Cite
|
Sign up to set email alerts
|

Immune response-associated production of neopterin. Release from macrophages primarily under control of interferon-gamma.

Abstract: Neopterin, a compound derived from GTP, represents a precursor molecule of biopterin that is an essential cofactor in neurotransmitter synthesis. We have recently reported that in vivo as well as in vitro immune responses are accompanied by an increased release of neopterin and that this phenomenon can be used for the biochemical monitoring of diseases accompanied by hyperimmune stimulation. This article deals with the cellular origin and the control of this immune response-associated neopterin release in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
447
2
4

Year Published

1990
1990
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,011 publications
(482 citation statements)
references
References 11 publications
15
447
2
4
Order By: Relevance
“…Furthermore, PCNSL tumor cells can secrete monocyte chemoattractant proteins which may induce the secretion of Npt from monocytes‐macrophages 30. Several studies have also reported that B lymphocytes can secrete Npt 31, 32. In the present study, we found that the CSF Npt concentration in patients with PCNSL was significantly higher than that in patients with other brain tumors and inflammatory diseases.…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, PCNSL tumor cells can secrete monocyte chemoattractant proteins which may induce the secretion of Npt from monocytes‐macrophages 30. Several studies have also reported that B lymphocytes can secrete Npt 31, 32. In the present study, we found that the CSF Npt concentration in patients with PCNSL was significantly higher than that in patients with other brain tumors and inflammatory diseases.…”
Section: Discussionsupporting
confidence: 57%
“…In this respect, our finding that circulating neopterin concentrations were higher in the vitamin A-deficient infants is intriguing. It is generally believed that elevated neopterin concentrations reflect increased macrophage activity, and this is regulated by IFN-g (Huber et al, 1984). How can this paradox of decreased ex vivo IFN-g production and increased in vivo neopterin concentrations be explained?…”
Section: Discussionmentioning
confidence: 99%
“…IDO induction is generally believed to represent a feedback mechanism of APC activation [8]. This understanding is supported by the observation that neopterin, a guanosine triphosphate (GTP) cleavage product [13], has been found to be closely linked to IDO activity in a wide spectrum of conditions involving immune activation [14][15][16].In some recent reports, also prostaglandin E2 (PGE 2 ) was described to up-regulate IDO competence in human DCs [17,18]. Induction of IDO competence through PGE 2 occurred, like in human DC maturation [19,20], in concert with TNF-α.…”
mentioning
confidence: 95%